What makes work meaningful? - Mortimer, Samuel A. (Journal of business ethics, 2023)
Prior scholarly approaches to meaningful work have largely fallen into two camps. One focuses on identifying how work can contribute to a meaningful life. The other studies the antecedents and outcomes of workers experiencing their work as meaningful. Neither of these approaches, however, captures what people look for when they seek meaningful work—or so I argue. In this paper, I give a new, commitment-based account of meaningful work by focusing on the reasons people have to choose meaningful work over other options. I draw on philosopher Ruth Chang’s account of voluntarist reasons (reasons that arise from an act of the will) to argue that commitments can create distinctive reasons to pursue certain work. It is the presence of these distinctive reasons that makes work meaningful.